Disruption of cellulose synthesis by 2, 6‐dichlorobenzonitrile affects the structure of the cytoskeleton and cell wall construction in Arabidopsis. (3rd July 2012) - Peng, L.; Zhang, L.; Cheng, X.; Fan, L.‐S.; Hao, H.‐Q.
Abstract Cellulose is the major component of plant cell walls and is an important source of industrial raw material. Although cellulose biosynthesis is one of the most important biochemical processes in plant biology, the regulatory mechanisms of cellulose synthesis are still unclear. Here, we report that 2, 6‐dichlorobenzonitrile (DCB), an inhibitor of cellulose synthesis, inhibits Arabidopsis root development in a dose‐ and time‐dependent manner. When treated with DCB, the plant cell wall showed altered cellulose distribution and intensity, as shown by calcofluor white and S4B staining. Moreover, pectin deposition was reduced in the presence of DCB when immunostained with the monoclonal antibody JIM5, which was raised against pectin epitopes. This result was confirmed using Fourier transform infrared (FTIR) analysis. Confocal microscopy revealed that the organisation of the microtubule cytoskeleton was significantly disrupted in the presence of low concentrations of DCB, whereas the actin cytoskeleton only showed changes with the application of high DCB concentrations. In addition, the subcellular dynamics of Golgi bodies labelled with N‐ST‐YFP and TGN labelled with VHA‐a1‐GFP were both partially blocked by DCB. Transmission electron microscopy indicated that the cell wall structure was affected by DCB, as were the Golgi bodies. Scanning electron microscopy showed changes in the organisation of cellulose microfibrils. These results suggest that the inhibition of cellulose synthesis by DCB not only induced changes in the chemical composition of the root cell wall and cytoskeleton structure, but also changed the distribution of cellulose microfibrils, implying that cellulose plays an important role in root development in Arabidopsis.